Smart companion robot for elderly care - Tan, Kok Fu (2025)
With the aging population and an increasing number of elderly people living alone, their wellbeing, health, and safety have been a big concern. Traditional monitoring systems such as CCTV cameras and panic buttons are at a disadvantage since they are fixed and dependent on human initiation. This project proposes the use of a multipurpose companion robot based on TurtleBot3 with autonomous movement integration, AI-based fall detection, live monitoring, and voice control. The robot will move autonomously throughout the home, continuously keeping an eye on the health of the elderly via an AI-driven camera system to detect falls, inactivity, or distress. It will also provide voice companionship and reminders to alleviate loneliness and improve mental health. A basic web interface will enable caregivers to remotely keep an eye on their loved ones, watch live video streams, and receive emergency alerts. The project involves creating and deploying deep learning-based fall detection models, speech recognition for two-way communication, and IoT integration for facilitating seamless data transmission. By integrating AI, IoT, and robotics, the project aims to develop an intelligent, cost-effective, and scalable solution that enhances elderly care, allows real-time safety monitoring, and facilitates emotional interaction, thus bridging the gap between technology and elderly care.